2015
DOI: 10.1007/s00220-014-2260-1
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Approach to Nonlocality and Contextuality

Abstract: Abstract. So far, most of the literature on (quantum) contextuality and the Kochen-Specker theorem seems either to concern particular examples of contextuality, or be considered as quantum logic. Here, we develop a general formalism for contextuality scenarios based on the combinatorics of hypergraphs which significantly refines a similar recent approach by Cabello, Severini and Winter (CSW). In contrast to CSW, we explicitly include the normalization of probabilities, which gives us a much finer control over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
432
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(436 citation statements)
references
References 90 publications
3
432
0
1
Order By: Relevance
“…Second, we apply pp-definability to the problem of quantum realizability of contextuality scenarios. Recently, Fritz [12] used Slofstra's results [24] to resolve two problems raised by Acin et al in [1]. Using pp-definability and Slofstra's results, we obtain new proofs of Fritz's results that have the additional feature that the parameters involved are optimal.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we apply pp-definability to the problem of quantum realizability of contextuality scenarios. Recently, Fritz [12] used Slofstra's results [24] to resolve two problems raised by Acin et al in [1]. Using pp-definability and Slofstra's results, we obtain new proofs of Fritz's results that have the additional feature that the parameters involved are optimal.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…Note that P 1-IN-3 SAT (X 1 , X 2 , X 3 ) = 3 4 X 1 X 2 X 3 + 1 4 X 1 X 2 + 1 4 X 2 X 3 + 1 4 X 1 X 3 − 1 4 X 1 − 1 4 X 2 − 1 4 X 3 + 1 4 , so the difference is that, even though the characteristic polynomial equation P 1-IN-3 SAT (X 1 , X 2 , X 3 ) = −I is satisfied by an operator assignment if and only if the resolution of the identity equation 1 2…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The near hexagon O − 8 (2) on 765 points is described in the text. (12,92,12,3) [120 28 , 1120 3 ] (3) , srg, NO + (8, 2), pg (7,8,4) 0.817 (15,99,11,6) [135 64 , 960 9 ] (3) , srg, G 4 , pg (8,7,4), 3QB * 0.770 (96,624,72,85) [960 36 , 4320 8 ] (4) 0.923 (4,6). Since the permutation representation is a subgroup of the modular group Γ = PSL(2, Z), it is possible to see the dessin D as an hyperbolic polygon D H .…”
Section: Orthogonalmentioning
confidence: 99%
“…Over the last few years, it has been recognized that the detailed investigation of commutation between the elements of generalized Pauli groups-the qudits and arbitrary collections of them [1]-is useful for a better understanding of the concepts of quantum information, such as error correction [2,3], entanglement [4,5] and contextuality [6][7][8], that are cornerstones of quantum algorithms and quantum computation. Only recently, the first author observed that much of the information needed is encapsulated in permutation representations, of rank larger than two, available in the Atlas of finite group representations [9].…”
Section: Introductionmentioning
confidence: 99%